NICA/ragüense: le documentaire comme témoignage socioculturel du phénomène d'immigration nicaraguayenne au Costa Rica - Andrea Cabezas Vargas (Les Cahiers ALHIM)
As a privileged source of visual and auditory memory, can documentary cinema serve as a reliable resource to reveal and to better understand the phenomenon of Nicaraguan immigration in Costa Rica? It is in focusing on this particular question that the article will analyze the documentary NICA/ragüense. This work is divided into three sections. The first part will address the subject of the documentary as both a social inquiry and a source of direct testimony. The second part will focus on the vision of the documentary NICA/ragüense being considered as a possible “counter-discourse” to the government and the national media. To conclude, the article will inquire about the contribution of this documentary to the demythification of the standard social discourse around the question of Nicaraguan immigration in Costa Rica.